Promoting Mental Health in Healthcare Workers in Hospitals Through Psychological Group Support With Eye Movement Desensitization and Reprocessing During COVID-19 Pandemic: An Observational Study - Fogliato, Elisa; Invernizzi, Roberta; Maslovaric, Giada; Fernandez, Isabel; Rigamonti, Vittorio; Lora, Antonio; Frisone, Enrico; Pagani, Marco (Frontiers in Psychology, 2022)
Background Psychological support was provided by the Eye Movement Desensitization and Reprocessing Integrative Group Treatment Protocol (EMDR-IGTP) within the hospitals in the Northern Italy in favor of healthcare workers during the COVID-19 pandemic. This study aimed at evaluating the effectiveness of treatment in terms of (a) symptomatology reduction related to peri- and post-traumatic stress; (b) clinical improvement over time; and (c) the maintenance of the achieved outcome over time. Methods The population was composed of healthcare workers who spontaneously requested psychological intervention in both the first and the second emergency waves. Statistical analyses were carried out to highlight the differences in Impact of Event-Revised (IES-R) and Post-Traumatic Growth Inventory (PTGI) before and after the group intervention. Results In both the first and the second waves, pre-treatment values are higher than post-treatment values for all dimensions of the IES-R. The results show that there are no significant differences between the first and the second wave with regard to the treatment effect. Healthcare workers maintained positive changes over time despite their prolonged exposure to an emergency and the possibility of retraumatization at the onset of a new emergency phase, irrespective of their working place. Healthcare workers who were treated in the first wave showed at the beginning of the second emergency wave less vulnerability and more resilience than those who were treated only in the second wave. Pre-treatment scores of healthcare workers affected by COVID-19 are discussed. Conclusion COVID-19 had a significant impact on the well-being of healthcare workers who were working in hospitals. Psychological support in case of emergency is needed.